A study on the wear of enamel caused by monolithic zirconia and the subsequent phase transformation compared to two other ceramic systems - Amreen Rupawala; Smita I Musani; Pallavi Madanshetty; Ramandeep Dugal; Umang D Shah; Ektaa J Sheth (The Journal of Indian Prosthodontic Society, 2017)
Purpose: The purpose of this in vitro research project was to evaluate and compare the wear behavior of human tooth enamel opposing monolithic zirconia and other different ceramic restorative materials and also to observe the tetragonal to monoclinic phase transformation in zirconia-based ceramics that may occur while simulating wear occurring at room temperature in a wet environment. Materials and Methods: A total of sixty samples were prepared for this study. Fifteen discs of glazed zirconia, 15 discs of polished zirconia without glaze, 15 discs of metal ceramic, and 15 discs of lithium disilicate were fabricated. Sixty extracted premolars were collected and randomly divided into four groups of 15 each. The discs and extracted human premolars were placed onto holders on a two-body wear machine under a constant load of 5 kg to simulate the oral wear cycle. A diffractometer was used to analyze phase transformation. One-way analysis of variance and Tukey's post hoc tests was used. Results: The mean loss of height of tooth samples and its standard deviation for Group I (monolithic zirconia with glaze), Group II (mechanically polished monolithic zirconia without glaze), Group III (porcelain fused to metal), and Group IV (glazed monolithic lithium disilicate) was obtained as 0.2716 ± 0.1409, 0.1240 ± 0.0625, 0.1567 ± 0.0996, and 0.2377 ± 0.1350, respectively. The highest mean loss in height was observed in Group I and the least was observed in Group II. Conclusion: Mechanically polished zirconia showed the least amount of enamel wear followed by porcelain fused to metal and glazed monolithic lithium disilicate, whereas glazed monolithic zirconia showed the highest enamel wear.